ANALISIS PENGARUH PENDEKATAN PERSONAL TENAGA PENJUAL, KUALITAS PRODUK, DAN HARGA TERHADAP KEPUASAN PELANGGAN - Priatno, Priatno (Jurnal Pilar Nusa Mandiri, 2014)
In a high level of a competitive environment, every business must maintain their customer. This study, therefore, intent to search several variables’ effect which is probably able to raise customer satisfaction. The study used several customers of PT PENERBIT ERLANGGA as a sample. Data analyze instrument used by the writer is SPSS 17. Data analyze result shows that the research model has well appropriateness and all hypothesis of the study are able to be evidenced. The summary said that personal approach of a salesperson, product quality and price are positively affected to customer satisfaction. Based on the result of the study, managerial implication given to the company is suggestion or input to the management of PT PENERBIT ERLANGGA to give more concern at the price, as it is the most dominant factor effected to customer satisfaction